RECONSTRUCTING CHARACTER EDUCATION THEORY THROUGH THE PERSPECTIVES OF PRIMARY SCHOOL TEACHERS IN INDONESIA: A GROUNDED THEORY STUDY - I Wayan Kandia; Ni Putu Ika Putri Sujianti; Adrianus Ahas (International Journal of Education and Social Science Studies, 2026)
This study aims to reconstruct a contextually grounded theory of character education based on Indonesian primary school teachers’ perspectives using grounded theory. Despite strong policy emphasis, existing models often fail to capture the cultural and pedagogical realities of Indonesian classrooms. Data were collected from approximately 25 primary school teachers across three provinces using interviews, observations, and document analysis. Data were analyzed using grounded theory procedures (open, axial, and selective coding) with constant comparison to achieve theoretical saturation. Findings indicate that character education is a dynamic, teacher-mediated process integrating curriculum, interaction, and local culture. The core category identified is contextualized teacher agency, supported by cultural integration, pedagogy, institutional support, and innovation. Teachers act as co-creators of moral development while balancing academic and ethical demands. The study also highlights challenges including limited resources, large class sizes, and the need for professional development, as well as innovative adaptations during remote learning contexts. This study proposes a culturally grounded framework and offers implications for curriculum, teacher training, and policy. It emphasizes teachers as key agents shaped by socio-cultural and structural contexts.